2002
DOI: 10.2307/3598659
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Governors on Veto Override Attempts: A Test of Pivotal Politics

Abstract: Using the "switcher" analysis developed by Krehbiel (1998), we examine the ability of Missouri governors to sway legislators on veto override attempts. Our initial results closely mirror Krehbiel's finding that the chief executive successfully achieves influence at and around the veto pivot, but these results change once we take into account the political party of the legislators. Governors are far more likely to influence legislators from their own party, regardless of legislator ideology. Our study provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…14. In a different setting (Wilkins and Young 2002), we found quite similar evidence on attempts to override gubernatorial vetoes.…”
Section: Notesmentioning
confidence: 52%
See 1 more Smart Citation
“…14. In a different setting (Wilkins and Young 2002), we found quite similar evidence on attempts to override gubernatorial vetoes.…”
Section: Notesmentioning
confidence: 52%
“…Specifically, we examine legislation considered under one of the most powerful procedural devices available in the House: closed rules. Since closed rules prohibit amendments on legislation, we can effectively use a "switcher analysis" (Krehbiel 1998;Wilkins and Young 2002) to compare votes on final passage of the legislation with the votes on the closed rule. Our analysis of all closed rule-final passage vote pairs for the 104th-108th Congresses reveals vote patterns that simply should not exist unless members are lending their leaders support on the procedural vote.…”
mentioning
confidence: 99%
“…Scholars have also found that governors use their veto power more frequently under a divided government as a consequence of proposed legislation not reflecting the politics of the governor's party (Klarner & Karch, 2008;Wiggins, 1980). In veto override situations, governors have indeed been found to be more likely to be able to influence a legislator belonging to the same party than a member from the opposition party, even under circumstances when two legislators do not disagree markedly regarding a policy (Wilkins & Young, 2002). Conflict between the branches, and subsequently more vetoes, may also occur when governors face a term limit.…”
Section: The Institutional Approachmentioning
confidence: 99%
“…Alternatively, and oftentimes in conjunction with the above approach, research has sought explanations to vetoes in the institutional factors such as term limits and variations in veto power (e.g. Baker & Hedge, 2013;Ferguson, 2003;Hedge, 1998;Herzik & Wiggins, 1989;Klarner & Karch, 2008;Wilkins & Young, 2002).…”
Section: Introductionmentioning
confidence: 99%